2021
DOI: 10.1158/1055-9965.epi-20-1652
|View full text |Cite
|
Sign up to set email alerts
|

Weight Regain and Breast Cancer–Related Biomarkers Following an Exercise Intervention in Postmenopausal Women

Abstract: Background: Epidemiologic studies have reported associations between weight fluctuations and postmenopausal breast cancer risk, however, the biological markers involved in this association are unknown. This study aimed to explore the associations between breast cancer-related biomarkers and weight regain following exercise-induced weight loss.Methods: From the 400 participants included in the Breast Cancer and Exercise Trial in Alberta, a total of 214 lost weight during the intervention and had follow-up blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Since these metabolic hormones are mainly released by adipose tissue, it has been reported that reductions in adiposity may be needed to reduce these biomarkers 32 . Previous studies in breast cancer survivors and breast cancer prevention have found strong associations between changes in MetS‐associated biomarkers and adiposity changes 24,38 . Our study found that after 8 weeks of HIIT, improvements in these biomarkers were independent of body composition changes in women undergoing breast cancer treatment.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Since these metabolic hormones are mainly released by adipose tissue, it has been reported that reductions in adiposity may be needed to reduce these biomarkers 32 . Previous studies in breast cancer survivors and breast cancer prevention have found strong associations between changes in MetS‐associated biomarkers and adiposity changes 24,38 . Our study found that after 8 weeks of HIIT, improvements in these biomarkers were independent of body composition changes in women undergoing breast cancer treatment.…”
Section: Discussionsupporting
confidence: 53%
“…36 We found significant reductions in CRP after HIIT. Additionally, MetS and hyperinsulinemia are associated with high levels of leptin and low levels of adiponectin, 37 which increased breast cancer cell growth and may increase breast cancer recurrence. 32 The HIIT intervention provides evidence of the effects of HIIT in reducing leptin and increasing adiponectin levels during breast cancer treatment.…”
Section: Discussionmentioning
confidence: 99%